2016
DOI: 10.15376/biores.11.4.shah
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Tensile Properties of Bamboo Fiber Reinforced Polymer Composites

Abstract: a This paper reviews the tensile properties of bamboo fiber reinforced polymer composites (BFRP). Environmentally friendly bamboo fibers have good mechanical properties, which make them suitable replacements for conventional fibers, such as glass and carbon, in composite materials. Better fiber and matrix interaction results in good interfacial adhesion between fiber/matrix and fewer voids in the composite. Several important factors improve matrix-fiber bonding and enhance the tensile properties of BFRP. Coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 43 publications
0
46
0
1
Order By: Relevance
“…Bamboo fiber is used for manufacturing bathroom products, decorating items, hygiene products, etc. [37,38]…”
Section: Bamboo Fibermentioning
confidence: 99%
“…Bamboo fiber is used for manufacturing bathroom products, decorating items, hygiene products, etc. [37,38]…”
Section: Bamboo Fibermentioning
confidence: 99%
“…Among the well‐known natural fiber plants, bamboo is by far one of the most promising reinforcements in biocomposites because of low density with high specific stiffness and strength. Bamboo fibers (BF) are constructed of cellulose microfibrils embedded in an amorphous matrix of hemicellulose and lignin, and they are also composed of bundles bound together with lignin . Recent work shows that such fibers extracted from the culms using a blasting extraction process have the superior tensile properties .…”
Section: Introductionmentioning
confidence: 99%
“…Both bamboo fibre and epoxy matrix are considered isotropic while the continuous BFRC is assumed to be transversely isotropic. The properties of bamboo fibres and epoxy matrix [30] used in this study are shown in Table II. The volume fraction of bamboo fibre may vary from 0 to 70%.…”
Section: A Materialsmentioning
confidence: 99%